Pengembangan Media Augmented Reality Berbasis Project Based Learning pada Materi Tata Surya - Rahma Diani; M. Rifatul Ickram; Sri Latifah (WISE Pendidikan Indonesia, 2026)
This study developed and evaluated an augmented reality (AR)-based physics learning medium integrated with the Project Based Learning (PjBL) model for the topic of the universe and solar system in grade X at SMA Negeri 8 Bandar Lampung. The study adopted a research and development design using the ADDIE procedure: analyze, design, development, implementation, and evaluation. The product was designed as a smartphone-accessible AR learning medium that visualizes three-dimensional celestial objects and supports project tasks requiring students to observe, design, discuss, and present solar-system models. Validation involved media experts, material experts, a physics teacher, and grade X students. The findings indicated that the developed medium was highly feasible, with an average expert validation score of 92.40%. Practicality responses from the teacher and students reached 93.10% and 89.70%, respectively, both categorized as very practical. Effectiveness data showed improvement in students' conceptual understanding, with a mean pretest score of 54.82, a mean posttest score of 82.46, and an N-gain of 0.61, indicating a moderate-to-high improvement. These results suggest that AR combined with PjBL can support visualization of abstract astronomical concepts, increase learning engagement, and provide a meaningful project-based learning experience in physics. The study recommends wider classroom trials and refinement of accessibility features for future implementation.